Enhanced dissolution of meloxicam from orodispersible tablets prepared by different methods - Ahmed Abd Elbary; Adel A. Ali; Heba M. Aboud (Faculty of Pharmacy, Cairo University, 2012)
The objective of this study was formulation, development and evaluation of meloxicam orodispersible tablets. ODTs were prepared by two methods including sublimation technique where different subliming agents like camphor, menthol and thymol were used with Ac-Di-Sol as a superdisintegrant. Each subliming agent was used in three different concentrations (5, 10 and 15% w/w). Tablets were first prepared and later exposed to vacuum. Meloxicam ODTs were also prepared by freeze-drying an aqueous dispersion of meloxicam containing a matrix former, a sugar alcohol, and a collapse protectant. In addition, different disintegration accelerators were tested (each in 1% w/v) including PVP K25, PVP K90, PEG 6000, PEG 4000, PEG 400, tween 80 and tween 20. The prepared ODTs from two methods were evaluated for weight variation, thickness, drug content, friability, hardness, wetting time, in vitro disintegration time and in vitro dissolution study. The best formulation was subjected to stability testing for 3 months at temperatures 40 °C and 75% relative humidity and at 60 °C. All formulations showed disintegration time ranging from 1 to 46 s. All the prepared formulae complied with the pharmacopoeial requirements of the drug contents. T17 gave the best in vitro disintegration and dissolution results. ODT formula T17 has shown no appreciable changes with respect to physical characters, meloxicam content and dissolution profiles when stored at elevated temperatures. In conclusion the results of this work suggest that orodispersible tablets of meloxicam with rapid disintegration time, fast drug release and good hardness can be efficiently and successfully formulated by employing freeze drying and sublimation methods.